1992
DOI: 10.1016/0378-4371(92)90248-o
|View full text |Cite
|
Sign up to set email alerts
|

Turing patterns in a simple gel reactor

Abstract: We introduce a very simple open two-dimensional gel reactor for studying chemical patterns that arise in reaction-diffusion systems. The reactor consists of a thin disk-shaped layer of polyvinyl alcohol gel with one face in direct contact with a well-stirred flow reactor containing reactants of the chlorite-iodide-malonic acid system; the other face of the gel is in contact with a piece of transparent plexiglass. We have used this reactor to study the transition from a uniform state to a hexagonal pattern; for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Another interesting example is a gel medium. There separate experiments revealed instability ( in particular Turing patterns ) [21] and sub-diffusion [3]. Thus one can expect observations of Turing instability in sub-diffusive gel solvents.…”
Section: There Exists a Ratiomentioning
confidence: 99%
“…Another interesting example is a gel medium. There separate experiments revealed instability ( in particular Turing patterns ) [21] and sub-diffusion [3]. Thus one can expect observations of Turing instability in sub-diffusive gel solvents.…”
Section: There Exists a Ratiomentioning
confidence: 99%
“…This value corresponds to the estimate of the timescale for diusion into and out of the gel. 9 The investigations performed have shown that the quality of images appearing in the media functioning in the gel matrix is signi®cantly better than in the case of the same reaction proceeding in the liquid phase. The gel matrix proved suitable for long-term repeated use after being washed with water.…”
Section: Reaction±diffusion Systems Based On Uniform Polymer Matricesmentioning
confidence: 98%
“…For example, employing the values of D u % 10 À9 (Reproduced from Ghiradella [1974] with permission). m 2 /s and q c % 10 4 m À1 to a gel reactor (Vigil et al, 1992), we estimated the diffusion constant as D u % 10 À15 m 2 /s for q c % 10 7 m À1 assuming the same reaction rate. Thus, the diffusion coefficient required for creating the color-producing pattern is estimated to be seven orders of magnitude smaller than that in water.…”
Section: Developmental Studies On Nanostructuresmentioning
confidence: 99%